Waterproof Device
A waterproof device with a water-repellent, air-permeable sheet enables air batteries to function in wet conditions by allowing air access, addressing the operational limitations of wearable medical patches in water exposure.
Patent Information
- Application Number
- JP2019514148
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-01-18
- Filing Date
- 2018-08-24
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2038-08-24
AI Technical Summary
Wearable medical devices like medical patches become inoperable when exposed to water due to the inability of air batteries to function if sealed, limiting power source options to non-air batteries that can't maintain long-term operation in wet conditions.
A waterproof device with a water-repellent, air-permeable sheet that allows air to reach the positive electrode of an air battery, ensuring it operates even when wet, using a configuration that stacks the battery and circuit section to minimize member count and maintain compactness.
The device maintains functionality in wet environments by allowing air to reach the air battery's positive electrode, ensuring long-term operation and reducing discomfort with a lightweight, compact design.
Smart Images

Figure 0007610924000005 
Figure 0007610924000006 
Figure 0007610924000007
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a waterproof device that is provided with water resistance and can also use an air battery as a power source. [Background technology]
[0002] In recent years, progress has been made in the development of small measuring devices that can be attached to the skin of a subject to measure biological information such as body temperature, respiratory rate, blood pressure, and heart rate, and can be used for health management, condition monitoring, treatment, and other purposes.
[0003] Known examples of such measuring devices include wearable patches, in which the entire device, which includes a sensor for measuring the necessary information, a communication means for transmitting the measured information to other devices, and a battery as a power source, can be attached to the human body using an adhesive layer or the like (Patent Documents 1 to 3, etc.).
[0004] In the medical field, such wearable patches are required to be disposable so that they can be disposed of as is after measurement, and it is desirable for the batteries used in wearable patches to be configured to have a small environmental impact.
[0005] The medical patch proposed in Patent Document 3 meets these demands and is constructed by laminating a sheet-shaped battery formed by a printing process that is disposable, has a low environmental impact, and is flexible, a flexible circuit equipped with a temperature sensor and a communication circuit, an adhesive layer that adheres to the skin, and a release liner. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Special Publication No. 2016-515022 [Patent Document 2] JP 2017-370 A [Patent Document 3] Special Publication No. 2016-505808 Summary of the Invention [Problem to be solved by the invention]
[0007] However, wearable medical devices, including medical patches, may be wetted or submerged in water during use, for example, when the subject bathes while wearing the device. In order to make the devices waterproof in anticipation of such cases, the exterior material of the wearable patch may seal the circuits and power source of the device parts of the patch, such as the sensor and communication means. Although alkaline batteries and lithium batteries can be used as power sources, it becomes impossible to use air batteries, which use air (oxygen) for the reaction at the positive electrode. In other words, air batteries, which are considered promising as power sources because they can be used for long periods of time, cannot be operated in a structure in which the power source and other parts are sealed with an exterior material, as air cannot be taken in to the positive electrode, and the types of batteries that can be used as power sources are limited.
[0008] The present disclosure has been made in consideration of the above circumstances, and has an object to provide a waterproof device that is water resistant and can also use an air battery as a power source. [Means for solving the problem]
[0009] In order to solve the above problems, the waterproof device disclosed in the present application is a device worn on the body, comprising a circuit unit, a power source, and an exterior body that protects the circuit unit and the power source, wherein at least a portion of the exterior body is made of a water-repellent, air-permeable sheet, and the water-repellent, air-permeable sheet has a water pressure resistance of 12 kPa or more. Effect of the Invention
[0010] The waterproof device disclosed in the present application is a waterproof device that can continue to operate in an environment in which it is wetted with water or immersed in water, even when it uses an air battery as a power source. [Brief description of the drawings]
[0011] [Figure 1] 1 is a cross-sectional view illustrating a schematic example of a waterproof device according to a first embodiment. [Diagram 2] FIG. 1 is a plan view illustrating an example of an air battery that can be used in the waterproof device according to the first embodiment. [Diagram 3] 1 is a cross-sectional view illustrating an example of an air battery that can be used in the waterproof device according to the first embodiment. [Figure 4] FIG. 11 is a cross-sectional view illustrating a schematic example of a waterproof device according to a second embodiment. [Diagram 5] FIG. 11 is a plan view illustrating a schematic example of a waterproof device according to a second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The waterproof device disclosed in the present application has a circuit unit, a power source, and an exterior body that protects the circuit unit and the power source, and can be worn on the body. Here, by forming at least a part of the exterior body from an air permeable sheet so that air and water vapor can pass through the exterior body, it becomes possible to supply air (oxygen) to the positive electrode when an air battery is used as a power source.
[0013] On the other hand, in order to prevent water from adhering to the circuit unit or the power source even when the waterproof device disclosed in the present application is wetted with water or immersed in water, it is necessary to make the breathable sheet of the exterior body water repellent. That is, by forming at least a part of the exterior body that protects the circuit unit and the power source from a water repellent breathable sheet, it is possible to protect the circuit unit and the power source from water droplets when the waterproof device is attached to the body. Therefore, when an air battery is used as a power source, it is possible to prevent water from entering the air hole formed in the storage container of the air battery and inhibiting the reaction of the positive electrode. In addition, it is also possible to diffuse water vapor emitted from the body to the outside through the water repellent breathable sheet, which is thought to be able to suppress the wearing part of the waterproof device from becoming stuffy and causing discomfort.
[0014] In order to ensure sufficient water resistance in the waterproof device disclosed in the present application, the water-repellent, gas-permeable sheet has a water pressure resistance of 12 kPa or more, preferably 15 kPa or more, which makes it possible to sufficiently prevent water from entering through the water-repellent, gas-permeable sheet and ensure the necessary water resistance even in situations in normal daily life where the wearer of the waterproof device gets wet, such as during bathing, or where a certain level of water pressure is applied underwater.
[0015] The upper limit of the water pressure resistance of the water-repellent, gas-permeable sheet is not particularly limited, but is usually about 800 kPa.
[0016] In this specification, the water pressure resistance of the water-repellent, air-permeable sheet is a value determined by JIS L 1092, Method B (high water pressure method).
[0017] In addition, the device disclosed in the present application preferably includes a functional element that contacts the skin, a drive circuit unit that operates the functional element, a sheet-shaped battery that is the power source in which a power generating element including a positive electrode and a negative electrode is enclosed inside two sheet-shaped battery exterior bodies, and an adhesive layer formed on the inner surface, and the sheet-shaped battery exterior body on the outer surface side of the sheet-shaped battery preferably constitutes a part of the exterior body that is the outer surface side of the entire exterior body. In this way, compared to a configuration in which a battery that is the operating power source and a drive circuit unit are arranged inside the exterior body that is the exterior body that constitutes the outer shell of the waterproof device, a simple configuration can be achieved in which the number of members that constitute the waterproof device is reduced. As a result, a waterproof device can be realized that maintains a small and lightweight form while using a sheet-shaped battery with a capacity necessary to perform the function, and does not cause discomfort to non-wearers.
[0018] In this specification, when the waterproof device is worn on the human body, the surface exposed to the outside is referred to as the outer surface, and the surface facing the skin of the human body is referred to as the inner surface.
[0019] In the waterproof device disclosed in the present application, it is preferable that the drive circuit section and the sheet-type battery are stacked, which makes it possible to increase the area of the sheet-type battery and thereby increase the battery capacity.
[0020] In addition, it is preferable that the battery is an air battery, and the water-repellent, gas-permeable sheet is disposed on a portion of the sheet-type battery exterior body disposed on the outer surface side facing the positive electrode. In this way, it is possible to realize a waterproof device with a simple configuration using a sheet-type battery that can increase the battery capacity per volume because oxygen in the air is used as a positive electrode active material.
[0021] Hereinafter, a waterproof device according to the present disclosure will be described with reference to the drawings.
[0022] Note that the drawings used to explain the structure of the waterproof device in this embodiment are intended to clearly explain the shapes of the components constituting the waterproof device and the interrelationships between their positions, and the sizes of the components shown in each drawing do not necessarily reflect their actual sizes.
[0023] (First embodiment) FIG. 1 is a cross-sectional view that illustrates a schematic example of a waterproof device according to a first embodiment of the present invention.
[0024] 1, the waterproof device 100 includes a drive circuit section 110, which is a circuit section formed on a substrate 122, and a battery 1, which is a power source, arranged on the drive circuit section 110, which are protected by an exterior body (outer shell member) 120 arranged on the outer surface side (the side opposite the body when the waterproof device is worn on the body). Note that in FIG. 1, the details of the battery 1 and the drive circuit section 110 are not shown in order to avoid cluttering the drawing.
[0025] The battery 1, together with the drive circuit section 110 constituting the main body of the waterproof device, is held in a space 123 formed by an exterior body 120 and a base material 122 arranged on the inner surface side (the side facing the skin of the human body), and is electrically connected to the drive circuit section 110. The base material 122 has an adhesive layer (bonding layer) 130, and can be directly attached to the body via this adhesive layer 130. Furthermore, the circuit section has a functional element 140 for detecting biological information such as the body temperature of the wearer of the waterproof device 100 and for performing some kind of processing on the wearer. The exterior body 120 is entirely composed of a water-repellent, breathable sheet 121.
[0026] Moreover, exterior body 120 is integrated with base material 122 by having its peripheral portion bonded to base material 122 by adhesive or thermal welding.
[0027] The material of the base material 122 is not particularly limited, but may be polyolefins such as polyethylene (PE) and polypropylene (PP), polyester, polyurethane, pulp, rayon, nylon, etc., and in order to maintain strength while allowing good moisture permeation, it is preferable that the thickness is, for example, about 20 to 600 μm.
[0028] A water-repellent, air-permeable sheet, which will be described later, may be used for the base material 122, and the exterior body 120 and the base material 122 may be made of the same material.
[0029] The water-repellent, gas-permeable sheet preferably has an air permeability of 60,000 sec / 100 ml or less, more preferably 6,000 sec / 100 ml or less. If the water-repellent, gas-permeable sheet has too low an air permeability, the strength of the sheet as an exterior material may be reduced or the sheet may not be able to provide the required water pressure resistance. Therefore, the water-repellent, gas-permeable sheet preferably has an air permeability of 20 sec / 100 ml or more.
[0030] The air permeability of the water-repellent, air-permeable sheet referred to in this specification is a value determined by the Gurley method specified in JIS P 8117.
[0031] The water-repellent, gas-permeable sheet constitutes part or all of the exterior body of the waterproof device, and since a certain degree of thickness tends to improve the usability of the waterproof device that is directly attached to the body, the thickness is preferably 0.01 mm or more, and more preferably 0.05 mm or more. However, if the water-repellent, gas-permeable sheet is too thick, for example, the waterproof device may become too thick and its usability may be impaired. Therefore, the thickness of the water-repellent, gas-permeable sheet is preferably 3 mm or less, more preferably 1 mm or less, and particularly preferably 0.5 mm or less.
[0032] The water-repellent, gas-permeable sheet may be composed only of a water-repellent porous sheet, or may be, for example, a laminated sheet in which a water-repellent porous sheet is laminated with a support sheet for ensuring strength.
[0033] When the water-repellent, gas-permeable sheet is composed only of a water-repellent porous sheet, or when the water-repellent porous sheet is a laminated sheet of a water-repellent porous sheet and a support sheet, examples of the water-repellent porous sheet include a porous sheet made of PE, PP, or polytetrafluoroethylene (PTFE) (such as a porous sheet used as a battery separator, a sheet having a large number of holes formed therein by a stretching method, etc.). The water-repellent porous sheet may have a single layer structure, or may have a multilayer structure in which, for example, two or more sheets made of different resins are laminated together.
[0034] When the water-repellent, gas-permeable sheet is a laminated sheet having a support sheet, examples of the support sheet include a nonwoven fabric sheet and a rubber sheet.
[0035] The nonwoven fabric sheet may be made of PE, PP, polyethylene terephthalate (PET), nylon, etc. The nonwoven fabric sheet may have a single layer structure or a multi-layer structure in which two or more nonwoven fabric sheets made of different resins are laminated.
[0036] Examples of the rubber sheet include a urethane rubber sheet, a silicone rubber sheet, etc. These rubber sheets may be porous, but since the rubber constituting these sheets has air permeability, they may be sheets without holes.
[0037] The porosity of the water-repellent porous sheet is not particularly limited as long as the water-repellent, gas-permeable sheet satisfies the above-mentioned water pressure resistance.
[0038] Furthermore, when the water-repellent, gas-permeable sheet is a laminated sheet of a water-repellent porous sheet and a support sheet, there are no particular restrictions on the thickness of the porous sheet and the support sheet, so long as the water-repellent, gas-permeable sheet as a whole satisfies the above-mentioned suitable thickness and satisfies the above-mentioned water pressure resistance.
[0039] For the water-repellent, breathable sheet, commercially available products such as "Breathlon" (product name) manufactured by Nitto Corporation, "Tyvek" (product name) manufactured by DuPont, "Poreflon" (product name) manufactured by Sumitomo Electric Industries, Ltd., "Gore-Tex" (product name) manufactured by WL Gore & Associates, Inc., and "TEMISH" (product name) manufactured by Nitto Denko Corporation can be used.
[0040] The exterior of the waterproof device may be entirely made of a water-repellent, gas-permeable sheet, or only a part of it may be made of a water-repellent, gas-permeable sheet as long as air and water vapor can sufficiently permeate through it. However, it is considered that the larger the ratio of the area made of the water-repellent, gas-permeable sheet to the entire area of the exterior, the greater the amount of air and water vapor that permeates per unit time, making it less likely to become stuffy when worn by a subject.
[0041] Furthermore, when an air battery is used as a power source, it is necessary to pass a certain amount of air per unit time in order to maintain good operating conditions of the air battery.
[0042] In view of the above, the proportion of the area of the water-repellent, air-permeable sheet in the entire area of the exterior body is preferably 10% or more, and more preferably 30% or more.
[0043] When an air battery is used as the power source, it is preferable to position the air battery so that an air hole in the storage container of the air battery faces the water-repellent, breathable sheet in order to efficiently take in air into the positive electrode of the air battery.
[0044] When only a portion of the exterior body of a waterproof device is made of a water-repellent, breathable sheet, the areas other than the area where the water-repellent, breathable sheet is arranged can be made of, for example, a non-perforated resin sheet (a sheet made of a resin such as PE, PP, polyethylene terephthalate, or nylon).
[0045] The battery used as the power source of the waterproof device is, for example, a battery that includes a positive electrode, a negative electrode, a separator, and an electrolyte housed in a container. There are no particular limitations on the type of battery, and any battery that can be used in small electronic devices can be used.
[0046] 2 and 3 show schematic diagrams of an example of an air battery that can be used in the waterproof device according to this embodiment. Fig. 2 is a plan view of the air battery. Fig. 3 is a cross-sectional view of the air battery. Fig. 3 shows a cross section of the part taken along line II in Fig. 2.
[0047] 2 and 3 is an example of a sheet-shaped air battery that contains a positive electrode 20, a negative electrode 30, a separator 40, and an electrolyte (not shown) in a sheet-shaped storage container 60, which is a sheet-shaped battery exterior body. The positive electrode 20 is connected to a positive electrode external terminal 21 via a lead body within the air battery 10, and although not shown, the negative electrode 30 is also connected to a negative electrode external terminal 31 via a lead body within the air battery 10.
[0048] As described later, the positive electrode of the air battery has a structure including, for example, a catalyst layer and a current collector, but in order to avoid complicating the drawing, the layers of the positive electrode 20 are not shown separately in Fig. 3. The dotted line in Fig. 2 indicates the size of the catalyst layer of the positive electrode 20 contained in the sheet-like container 60.
[0049] The sheet-like storage container 60 has a plurality of air holes 61 for taking in air to the positive electrode on the side where the positive electrode 20 is arranged, and a water-repellent film 50 for preventing leakage of electrolyte from the air holes 61 is arranged on the inside.
[0050] The positive electrode (air electrode) of the air battery has a catalyst layer, and for example, a structure in which a catalyst layer and a current collector are laminated can be used.
[0051] The catalyst layer may contain a catalyst, a binder, and the like.
[0052] Examples of the catalyst for the catalyst layer include silver, platinum group metals or alloys thereof, transition metals, platinum / metal oxides such as Pt / IrO2, La 1-x Ca x Examples include perovskite oxides such as CoO3, carbides such as WC, nitrides such as Mn4N, manganese oxides such as manganese dioxide, and carbon (graphite, carbon black (acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, etc.), charcoal, activated carbon, etc.), and one or more of these are used.
[0053] The catalyst layer preferably contains 1% by mass or less of heavy metals, excluding the components of the electrolyte. In the case of a positive electrode having a catalyst layer with such a low content of heavy metals, the battery can be disposed of without any special treatment, resulting in a battery with low environmental impact.
[0054] The content of heavy metals in the catalyst layer can be measured by fluorescent X-ray analysis. For example, it can be measured using Rigaku's "ZSX100e" under the conditions of excitation source: Rh50kV, and analysis area: φ10mm.
[0055] Therefore, it is recommended that the catalyst for the catalyst layer not contain heavy metals, and it is more preferable to use the various carbons mentioned above.
[0056] In order to further increase the reactivity of the positive electrode, the specific surface area of the carbon used as the catalyst is set to 200 m 2 / g or more, and 2 / g or more is more preferable, and 500m 2 / g or more is more preferable. The specific surface area of carbon in this specification is a value determined by the BET method in accordance with JIS K 6217, and can be measured, for example, using a specific surface area measuring device ("Macsorb HM model e-1201" manufactured by Mountech Co., Ltd.) using the nitrogen adsorption method. The upper limit of the specific surface area of carbon is usually 2000 m 2 / g.
[0057] The catalyst content in the catalyst layer is preferably 20 to 70 mass %.
[0058] Examples of the binder for the catalyst layer include fluororesin binders such as polyvinylidene fluoride (PVDF), PTFE, copolymers of vinylidene fluoride, and copolymers of tetrafluoroethylene (vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), vinylidene fluoride-chlorotrifluoroethylene copolymer (PVDF-CTFE), vinylidene fluoride-tetrafluoroethylene copolymer (PVDF-TFE), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer (PVDF-HFP-TFE), etc.). Among these, tetrafluoroethylene polymer (PTFE) or copolymer is preferred, and PTFE is more preferred. The content of the binder in the catalyst layer is preferably 3 to 50 mass%.
[0059] The positive electrode can be manufactured, for example, by mixing the catalyst, binder, etc. with water, rolling the mixture with a roll, and adhering it to a current collector. Alternatively, the positive electrode can be manufactured through a process in which a catalyst layer forming composition (slurry, paste, etc.) prepared by dispersing the catalyst and a binder to be used as needed in water or an organic solvent is applied to the surface of a current collector, dried, and then subjected to a pressing process such as a calendaring process as necessary.
[0060] The positive electrode current collector may be, for example, a metal mesh, foil, expanded metal, or punched metal such as titanium, nickel, stainless steel, or copper; a carbon mesh or sheet; etc. The thickness of the positive electrode current collector is preferably 10 μm or more and 300 μm or less.
[0061] In the case of an air battery having a sheet-like container, the current collector of the positive electrode can be a part of a resin film constituting the sheet-like container or a laminate of a resin film and a metal film. In this case, for example, a carbon paste can be applied to the surface of the resin film or the laminate that is expected to become the inner surface of the sheet-like container to form a current collector, or a metal layer of the laminate can be used as a current collector, and a positive electrode mixture layer or a catalyst layer can be formed on this surface in the same manner as above to form a positive electrode. The thickness of the carbon paste layer is preferably 30 to 300 μm.
[0062] For the negative electrode of the air battery, for example, metal particles or metal foils made of metal materials such as zinc-based materials (a collective term for zinc materials and zinc alloy materials), magnesium-based materials (a collective term for magnesium materials and magnesium alloy materials), aluminum-based materials (a collective term for aluminum materials and aluminum alloy materials), etc. In such negative electrodes, metals such as zinc, magnesium, and aluminum act as active materials.
[0063] Examples of alloy components of the zinc alloy material include indium (eg, a content of 0.005 to 0.05% by mass), bismuth (eg, a content of 0.005 to 0.05% by mass), and aluminum (eg, a content of 0.001 to 0.15% by mass).
[0064] Examples of alloy components of magnesium alloy materials include calcium (e.g., a content of 1 to 3% by mass), manganese (e.g., a content of 0.1 to 0.5% by mass), zinc (e.g., a content of 0.4 to 1% by mass), and aluminum (e.g., a content of 8 to 10% by mass).
[0065] Further, examples of alloy components of the aluminum alloy material include zinc (e.g., a content of 0.5 to 10% by mass), tin (e.g., a content of 0.04 to 1.0% by mass), gallium (e.g., a content of 0.003 to 1.0% by mass), silicon (e.g., a content of 0.05% or less by mass), iron (e.g., a content of 0.1% or less by mass), magnesium (e.g., a content of 0.1 to 2.0% by mass), and manganese (e.g., a content of 0.01 to 0.5% by mass).
[0066] In the case of a negative electrode containing metal particles, the metal particles may be of one type alone or of two or more types.
[0067] In addition, in consideration of reducing the environmental load when disposing of batteries, it is preferable that the metal material used for the negative electrode contains small amounts of mercury, cadmium, lead, and chromium, and it is more preferable that the specific contents, on a mass basis, are mercury: 0.1% or less, cadmium: 0.01% or less, lead: 0.1% or less, and chromium: 0.1% or less.
[0068] Regarding the particle size of the particles made of zinc-based materials, for example, the proportion of particles having a particle size of 75 μm or less among all particles is preferably 50 mass% or less, more preferably 30 mass% or less, and the proportion of particles having a particle size of 100 to 200 μm is 50 mass% or more, more preferably 90 mass% or more.
[0069] Regarding the particle size of the particles composed of magnesium-based and aluminum-based materials, for example, the proportion of particles having a particle size of 30 μm or less among all particles is preferably 50 mass% or less, more preferably 30 mass% or less, and the proportion of particles having a particle size of 50 to 200 μm is 50 mass% or more, more preferably 90 mass% or more.
[0070] The particle size of metal particles in this specification is the particle size at a cumulative frequency of 50% on a volume basis, measured by dispersing the particles in a medium that does not dissolve the particles using a laser scattering particle size distribution analyzer (e.g., HORIBA LA-920).50 ).
[0071] In the case of the negative electrode containing the metal particles, a thickener (sodium polyacrylate, CMC (particularly, CMC having a degree of etherification described below, suitable as a thickener for electrolytes), etc.) may be added as necessary, and a binder may be added to the electrolyte to form a negative electrode agent (such as a gelled negative electrode). The amount of the thickener in the negative electrode is preferably, for example, 0.5 to 1.5% by mass, and the amount of the binder is preferably 0.5 to 3% by mass.
[0072] The electrolytic solution for the negative electrode containing metal particles can be the same as that injected into the battery (the electrolytic solution used as the electrolyte).
[0073] The content of metal particles in the negative electrode is, for example, preferably 60% by mass or more, more preferably 65% by mass or more, and is preferably 95% by mass or less, more preferably 90% by mass or less.
[0074] The negative electrode containing metal particles preferably contains an indium compound, which makes it possible to more effectively prevent hydrogen gas generation due to a corrosion reaction between the metal particles and the electrolyte.
[0075] Examples of the indium compound include indium oxide and indium hydroxide.
[0076] The amount of the indium compound used in the negative electrode is preferably 0.003 to 1 per 100 metal particles in terms of mass ratio.
[0077] In the case of a negative electrode using a metal foil, the thickness is preferably 10 to 500 μm.
[0078] In addition, a current collector may be used for the negative electrode as necessary. Examples of the current collector for the negative electrode include a mesh, foil, expanded metal, punched metal, etc., of a metal such as nickel, copper, or stainless steel; a carbon sheet or mesh; etc. The thickness of the current collector for the negative electrode is preferably 10 μm or more and 300 μm or less.
[0079] In the case of an air battery having a sheet-like container, the negative electrode current collector may be formed by applying a carbon paste to the surface that is to become the inner surface of the sheet-like container, or may be formed of a metal layer that constitutes the sheet-like container, as in the case of the positive electrode. The thickness of the carbon paste layer is preferably 50 to 200 μm.
[0080] Examples of separators for air batteries include separators commonly used in various batteries, such as resin porous membranes (microporous membranes, nonwoven fabrics, etc.) and semipermeable membranes such as cellophane films. From the viewpoint of preventing short circuits and improving the load characteristics of air batteries, it is preferable to use semipermeable membranes as separators.
[0081] Examples of the resin that constitutes the separator made of a resin porous film include polyolefins such as PE, PP, and ethylene-propylene copolymers.
[0082] In the case of a resin separator, the porosity is preferably 30 to 80%, and the thickness is preferably 10 to 100 μm.
[0083] In addition, when a semipermeable membrane such as a cellophane film is used as the separator, the separator may be composed of only the semipermeable membrane. However, since the semipermeable membrane has a low strength, problems such as breakage during battery assembly are likely to occur. Therefore, it is also recommended to compose the separator with a laminate in which a graft film composed of a specific polymer and a semipermeable membrane are laminated.
[0084] The graft polymer constituting the graft film has a form in which (meth)acrylic acid or its derivatives are graft-polymerized onto a polyolefin (polyethylene, polypropylene, etc.) trunk polymer, for example. However, the graft polymer may have the above-mentioned form, and does not have to be produced by a method of graft-polymerizing (meth)acrylic acid or its derivatives onto a polyolefin.
[0085] The (meth)acrylic acid or its derivative constituting the graft polymer is represented by the following general formula (1). 1 is H or CH3, R 2 means H or a hydrophilic substituent such as NH4, Na, K, Rb, or Cs.
[0086] [ka]
[0087] The polymer constituting the graft film and cellophane film has the function of absorbing an electrolyte (electrolytic solution) and allowing ions to pass through.
[0088] The graft polymer constituting the graft film preferably has a graft ratio defined by the following formula (2) of 160% or more. Since there is a correlation between the graft ratio of the graft polymer and the electrical resistance of the graft film, by using a graft polymer having a graft ratio as described above, the electrical resistance of the graft film can be increased to 20 to 120 mΩ·in 2 The electrical resistance of the graft film is a value obtained by an AC voltage drop method (1 kHz). The atmospheric temperature is set to 20 to 25°C, the film is immersed in a 40% KOH (specific gravity: 1.400±0.005) aqueous solution at 25±1°C, and after 5 to 15 hours, it is taken out and the electrical resistance is measured.
[0089] Graft rate (%) = 100 × (AB) / B (2) In the formula (2), A is the mass (g) of the graft polymer, and B is the mass (g) of the trunk polymer in the graft polymer. In the formula (2), "B (the mass of the trunk polymer in the graft polymer)" is, for example, when the graft polymer is formed by graft polymerization of (meth)acrylic acid or its derivatives to a polyolefin trunk polymer, the mass of the trunk polymer used in the graft polymerization may be measured in advance. In the graft polymer, the graft ratio may exceed 100% because the monomers used in the graft polymerization [(meth)acrylic acid or its derivatives] may polymerize with each other, resulting in a long chain of graft molecules. The upper limit of the graft ratio of the graft polymer defined by the formula (2) is preferably 400%. In addition, the "(meth)acrylic acid" is a collective expression of acrylic acid and methacrylic acid.
[0090] In the case of a separator formed only of a cellophane film, the thickness is, for example, preferably 15 μm or more and preferably 40 μm or less, and more preferably 30 μm or less.
[0091] Furthermore, in the case of a separator composed of a laminate of a graft film and a cellophane film, the total thickness of the graft film and the cellophane film is, for example, preferably 30 μm or more, more preferably 40 μm or more, and preferably 70 μm or less, more preferably 60 μm or less.
[0092] Furthermore, in the case of a separator formed of a laminate of a graft film and a cellophane film, the thickness of the graft film is, for example, preferably 15 μm or more, more preferably 25 μm or more, and preferably 30 μm or less.
[0093] Examples of laminates of a graft film and a cellophane film for forming a separator include those commercially available from Yuasa Membrane Systems Co., Ltd. under the names "YG9132", "YG9122", and "YG2152".
[0094] Alternatively, the separator may be formed by combining a cellophane film, or a combination of a cellophane film and a graft film with a liquid-absorbing layer (electrolyte solution retaining layer) such as vinylon-rayon mixed paper. The thickness of such a liquid-absorbing layer is preferably 20 to 500 μm.
[0095] For example, an aqueous solution (electrolyte) containing an electrolyte salt is used as the electrolyte of the air battery. The aqueous solution used as the electrolyte preferably has a pH of 3 or more, more preferably 5 or more, and preferably less than 12, more preferably 10 or less, and even more preferably less than 7. By using an aqueous solution with such a pH, problems are less likely to occur even if the electrolyte adheres to the human body due to damage during disposal or use of the air battery (waterproof device having an air battery), and high safety can be ensured and the burden on the environment after disposal can be reduced, compared to the case of using an alkaline aqueous solution with a high pH (about pH 14) that is a strong alkali commonly used in air batteries.
[0096] Examples of electrolyte salts dissolved in the aqueous solution used as an electrolyte include chlorides such as sodium chloride, potassium chloride, magnesium chloride, calcium chloride, ammonium chloride, and zinc chloride; hydroxides of alkali metals and alkaline earth metals (sodium hydroxide, potassium hydroxide, magnesium hydroxide, etc.), acetates (sodium acetate, potassium acetate, magnesium acetate, etc.), nitrates (sodium nitrate, potassium nitrate, magnesium nitrate, etc.), sulfates (sodium sulfate, potassium sulfate, magnesium sulfate, etc.), and phosphates (sodium phosphate, potassium phosphate, magnesium phosphate, etc.). , borates (sodium borate, potassium borate, magnesium borate, etc.), citrates (sodium citrate, potassium citrate, magnesium citrate, etc.), glutamate (sodium glutamate, potassium glutamate, magnesium glutamate, etc.); alkali metal bicarbonates (sodium bicarbonate, potassium bicarbonate, etc.); alkali metal percarbonates (sodium percarbonate, potassium percarbonate, etc.); compounds containing halogens such as fluorides; polycarboxylic acids; and the aqueous solution may contain one or more of these electrolyte salts.
[0097] As the electrolyte salt, a salt of a strong acid selected from hydrochloric acid, sulfuric acid, and nitric acid and a weak base represented by ammonia or a hydroxide of a metal element such as aluminum hydroxide or magnesium hydroxide is preferable, and it is more preferable to use an ammonium salt or a salt of a specific metal element. - , SO4 2- , HSO4 - and NO3 -and at least one ion selected from Al ion, Mg ion, Fe ion, and ammonium ion. Examples of such ions include ammonium salts such as ammonium sulfate, ammonium hydrogen sulfate [(NH4)HSO4], ammonium chloride, and ammonium nitrate; aluminum salts such as aluminum sulfate, aluminum chloride, and aluminum nitrate; magnesium salts such as magnesium sulfate, magnesium chloride, magnesium chloride hydroxide [MgCl(OH)], and magnesium nitrate; and iron salts such as iron (II) sulfate, ammonium iron (II) sulfate [(NH4)2Fe(SO4)2], iron (III) sulfate, iron (II) chloride, and iron (II) nitrate.
[0098] The electrolyte made of an aqueous solution containing the above-mentioned salt of a strong acid and a weak base has a relatively small effect of corroding the metal or alloy that is the negative electrode active material, compared to an electrolyte containing a salt of a strong acid and a strong base such as sodium chloride. Also, among the salts of strong acids, an electrolyte containing a salt of a metal element selected from Al, Mg, and Fe or an ammonium salt has a relatively high electrical conductivity compared to, for example, an aqueous solution of zinc chloride. Therefore, as a salt of a strong acid and a weak base, Cl - , SO4 2- , HSO4 - and NO3 - At least one ion selected from the group consisting of A When an electrolyte consisting of an aqueous solution containing a salt with at least one ion selected from the group consisting of l ions, Mg ions, Fe ions, and ammonium ions is used, the discharge characteristics of the air battery can be further improved.
[0099] However, Cl - ions and Fe 3+ Regarding salts with ions [iron(III) chloride], since iron(III) chloride has a stronger corroding effect on the metal material that is the negative electrode active material than salts with other ion combinations, it is preferable to use a salt other than iron(III) chloride, and it is more preferable to use an ammonium salt since it has a lower corroding effect on the metal material that is the negative electrode active material.
[0100] Moreover, among the salts of the strong acid and the weak base, perchlorates pose a risk of combustion or explosion when heated or impacted. From the viewpoint of environmental load and safety during disposal, therefore, it is preferable that the aqueous solution does not contain perchlorate ions, or that the amount of perchlorate ions contained therein is small (preferably less than 100 ppm, and more preferably less than 10 ppm).
[0101] Furthermore, among the salts of strong acids and weak bases, many heavy metal salts (excluding iron salts), such as zinc chloride and copper sulfate, are harmful. From the viewpoint of environmental load and safety during disposal, it is preferable that they are not contained in the aqueous solution, or that even if they are contained, the amount of heavy metal ions other than iron ions is small (preferably less than 100 ppm, and more preferably less than 10 ppm).
[0102] In addition, the aqueous solution usable as the electrolyte preferably contains a water-soluble high-boiling point solvent having a boiling point of 150° C. or higher as a solvent together with water. In an air battery, when the capacity decreases due to discharge, the voltage decreases accordingly, but in the later stage of discharge when the capacity decreases, the voltage tends to fluctuate in addition to decreasing. However, when the aqueous solution contains a water-soluble high-boiling point solvent, the voltage fluctuation in the later stage of discharge can be suppressed, resulting in an air battery with better discharge characteristics.
[0103] 2 and 3, the air battery has an air hole in the container for introducing air to the positive electrode, but the water in the electrolyte (electrolytic solution) volatilizes and dissipates through the air hole in the container, which can easily cause fluctuations in the electrolyte composition and can lead to a deterioration in discharge characteristics. However, when the aqueous solution used as the electrolyte contains a water-soluble high-boiling point solvent, the evaporation of water from the electrolyte is suppressed, making it possible to suppress the deterioration in discharge characteristics caused by the electrolyte composition fluctuations, and also to further improve the storage characteristics of the air battery.
[0104] The upper limit of the boiling point of the water-soluble high-boiling point solvent is usually 320°C.
[0105] From the viewpoint of maintaining the discharge characteristics of the air battery better, it is desirable that the water-soluble high-boiling point solvent has a high surface tension and a high dielectric constant. In the air battery, the positive electrode (catalyst layer) needs to come into contact with air during discharge, but if the surface tension of the water-soluble high-boiling point solvent in the electrolyte is low, the proportion of the surface of the catalyst-containing layer of the positive electrode that is covered with the electrolyte and is difficult to come into contact with air becomes too large, which may result in a deterioration of the discharge characteristics. However, by using a water-soluble high-boiling point solvent with a high surface tension, such a problem can be avoided.
[0106] Furthermore, since organic solvents usually have a lower dielectric constant than water, when an electrolyte is prepared by using an organic solvent in combination with water, the ionic conductivity is lower than when water alone is used, and there is a risk of impairing the discharge characteristics of the battery. However, the occurrence of such problems can be suppressed by using a water-soluble high-boiling point solvent with a high dielectric constant.
[0107] Specifically, the surface tension of the water-soluble high-boiling point solvent is preferably 30 mN / m or more. The upper limit of the surface tension of the water-soluble high-boiling point solvent is usually 70 mN / m. The surface tension of the water-soluble high-boiling point solvent referred to in this specification is a value measured by the Wilhelmy method using a commercially available device (for example, "CBVP-Z" manufactured by Kyowa Interface Science Co., Ltd.).
[0108] Furthermore, the relative dielectric constant of the water-soluble high-boiling point solvent is preferably 30 or more. The upper limit of the relative dielectric constant of the water-soluble high-boiling point solvent is usually 65. The relative dielectric constant of the water-soluble high-boiling point solvent referred to in this specification is a value determined from the dielectric constant measured using a Hewlett-Packard "Presion LCR Meter HP4284" or the like.
[0109] Specific examples of water-soluble high-boiling point solvents suitable for the electrolyte include polyhydric alcohols such as ethylene glycol (boiling point 197°C, surface tension 48mN / m, dielectric constant 39), propylene glycol (boiling point 188°C, surface tension 36mN / m, dielectric constant 32), and glycerin (boiling point 290°C, surface tension 63mN / m, dielectric constant 43); and polyalkylene glycols such as polyethylene glycol (PEG; for example, boiling point 230°C, surface tension 43mN / m, dielectric constant 35) (preferably with a molecular weight of 600 or less). Only one of these water-soluble high-boiling point solvents may be used for the electrolyte, or two or more of them may be used in combination, but it is more preferable to use glycerin.
[0110] When using a water-soluble high-boiling point solvent, from the viewpoint of ensuring the effect of its use, the content of the water-soluble high-boiling point solvent in the total solvent of the aqueous solution is preferably 1% by mass or more, more preferably 3% by mass or more. However, if the amount of the water-soluble high-boiling point solvent in the aqueous solution is too large, the ionic conductivity of the aqueous solution may become too small, which may deteriorate the battery characteristics, so the content of the water-soluble high-boiling point solvent in the total solvent of the aqueous solution is preferably 30% by mass or less, more preferably 20% by mass or less.
[0111] The concentration of the electrolyte salt in the aqueous solution may be any concentration that allows the electrical conductivity of the aqueous solution to be adjusted to about 80 to 700 mS / cm, and is usually 5 to 50 mass %.
[0112] The aqueous solution used as the electrolyte preferably contains an indium compound dissolved in its solvent (water or a mixed solvent of water and a water-soluble high-boiling point solvent).When an indium compound is dissolved in the aqueous solution, the generation of hydrogen gas in the battery can be effectively suppressed.
[0113] Examples of the indium compound to be dissolved in the aqueous solution include indium hydroxide, indium oxide, indium sulfate, indium sulfide, indium nitrate, indium bromide, and indium chloride.
[0114] The concentration of the indium compound in the aqueous solution is, by mass, preferably 0.005% or more, more preferably 0.01% or more, and particularly preferably 0.05% or more, and is preferably 1% or less, more preferably 0.5% or less, and particularly preferably 0.1% or less.
[0115] In addition to the above-mentioned components, various known additives may be added to the aqueous solution as necessary within the range that does not impair the effects of the present invention. For example, zinc oxide may be added to prevent corrosion (oxidation) of the metal material used in the negative electrode.
[0116] The aqueous solution constituting the electrolyte may be gelled, and it is also preferable to use a gelled electrolyte obtained by blending an aqueous solution containing an electrolyte salt and having a pH of 3 or more and less than 12 with a thickener as the electrolyte for the air battery. In this case as well, it is possible to suppress fluctuations in voltage in the later stage of discharge and further improve the discharge characteristics of the air battery, and since the volatilization of water from the gelled electrolyte is suppressed, it is possible to suppress deterioration of the discharge characteristics due to fluctuations in the electrolyte composition, and it is also possible to further improve the storage characteristics of the air battery.
[0117] For the aqueous solution containing an electrolyte salt and having a pH of 3 or more and less than 12 related to the gel electrolyte, the same aqueous solutions as those exemplified above as those usable as the electrolyte for the air battery can be used.
[0118] Examples of thickeners for forming a gel electrolyte include cellulose derivatives such as carboxymethylcellulose (CMC) and carboxyethylcellulose (CEC); polyalkylene glycols such as polyethylene glycol (PEG) (preferably with a molecular weight of 10,000 or more); polyvinylpyrrolidone; polyvinyl acetate; starch; guar gum; xanthan gum; sodium alginate; hyaluronic acid; gelatin; and various synthetic or natural polymers. To form a gel electrolyte, only one of the above-mentioned thickeners may be used, or two or more may be used in combination. Note that polyalkylene glycols such as PEG are generally commercially available with their molecular weights (average molecular weights) clearly indicated, and the molecular weight of the polyalkylene glycols referred to in this specification refers to the nominal value of such manufacturers.
[0119] Among the above-mentioned thickeners, CMC, xanthan gum, and high molecular weight PEG (molecular weight of 100,000 or more, preferably 5,000,000 or less) are more preferred because they have a high thickening effect on the electrolyte (electrolytic solution, which is an aqueous solution of an electrolyte salt) and can more easily prepare a gel electrolyte with good properties.
[0120] In addition, CMC is an anionic polymer, and is easily affected by metal ions and salts when they coexist, so the thickening effect of the electrolyte may be reduced. However, when the degree of etherification of CMC is high, it is less affected by metal ions and salts, and the thickening effect of the electrolyte can be better exhibited. Specifically, the degree of etherification of CMC is preferably 0.9 or more, and more preferably 1.0 or more. The degree of etherification of CMC here is a value that indicates how many carboxymethyl groups are ether-bonded per anhydroglucose unit. In addition, the degree of etherification of CMC is preferably 1.6 or less.
[0121] Furthermore, when using a thickener having a functional group (-COOH, -COONa, etc.) consisting of a carboxyl group or its salt in the molecule, such as CMC, CEC, xanthan gum, or sodium alginate, it is preferable to blend a polyvalent metal salt acting as a gelation accelerator with the electrolyte. In this case, the gelation accelerator acts on the thickener, so that the electrolyte gels better, making it easier to form a gel electrolyte with good properties.
[0122] The polyvalent metal salt usable as the gelation accelerator varies depending on the type of thickener used, but is preferably a salt of a divalent or trivalent metal ion, and examples thereof include alkaline earth metal salts such as magnesium salts (magnesium sulfate, etc.) and calcium salts (calcium sulfate); aluminum salts such as aluminum nitrate and aluminum sulfate; iron salts such as iron chloride (II), iron chloride (III), and iron sulfate (III); and chromium salts such as chromium nitrate. Among these, aluminum salts and iron salts are more preferable. It is desirable to use an aqueous solution having a pH of 3 or more and less than 12 to form a gel electrolyte, thereby reducing the environmental load caused by the battery, and when aluminum salts or iron salts are used as the gelation accelerator, the increase in the environmental load caused by the gelation accelerator can be suppressed.
[0123] Depending on the combination of the electrolyte salt and the thickener, the electrolyte salt itself may act as a gelation promoter, making it impossible to form a homogeneous gel electrolyte or to form a gel electrolyte with sufficient ion conductivity. In such cases, the above problem can be prevented by using only a monovalent metal ion salt as the electrolyte salt, using a polyvalent metal ion salt and a monovalent metal ion salt in combination, or separately preparing an aqueous solution containing an electrolyte salt and an aqueous solution containing a thickener, and then mixing them to prepare an electrolyte. It is also preferable to use an ammonium salt as the electrolyte salt.
[0124] From the viewpoint of ensuring good ion conductivity while making the electrolyte a good gel, the amount of thickener in the electrolyte is preferably 0.1% by mass or more, and more preferably 0.2% by mass or more, and is preferably 5% by mass or less, and more preferably 3% by mass or less.
[0125] Furthermore, when a polyvalent metal salt serving as a gelation accelerator is blended in the electrolyte, the blending amount of the polyvalent metal salt, from the viewpoint of better exerting its function, is preferably 1 or more, and more preferably 2 or more, when the ratio of the thickener is taken as 100 by mass. Even if the blending amount of the polyvalent metal salt is increased, the effect becomes saturated, so the blending amount of the polyvalent metal salt in the electrolyte is preferably 30 or less, and more preferably 20 or less, when the ratio of the thickener is taken as 100 by mass.
[0126] When the electrolyte salt also serves as a gelation accelerator, the amount of the gelation accelerator may be set within the above-mentioned suitable concentration range of the electrolyte salt.
[0127] The aqueous solution containing the electrolyte salt used as the electrolyte may be prepared by adding necessary components (such as the electrolyte salt, a water-soluble high-boiling point solvent used as needed, and an indium compound) to water and dissolving them.
[0128] Furthermore, the gel electrolyte can be formed, for example, by dissolving a thickener and other components (such as an indium compound) used as necessary in an aqueous solution containing a previously prepared electrolyte salt and having a pH of 3 or more and less than 12. Furthermore, when a water-soluble high-boiling point solvent is used, for example, water and the water-soluble high-boiling point solvent are mixed, and the aqueous solution is prepared using this mixed solvent, and this may be used to form the gel electrolyte.
[0129] In addition, when a thickener having a functional group consisting of a carboxyl group or its salt in the molecule and a polyvalent metal salt acting as a gelation promoter are used in the gel electrolyte, it is preferable to form the gel electrolyte by a method of mixing an aqueous solution containing an electrolyte salt and having a pH of 3 or more and less than 12, in which a thickener is further dissolved, and an aqueous solution in which a gelation promoter (polyvalent metal salt) is dissolved. When such a preparation method is adopted, the gel electrolyte can be formed better than a method of adding a thickener and a polyvalent metal salt to an aqueous solution containing an electrolyte salt and having a pH of 3 or more and less than 12. Furthermore, it is particularly preferable to inject an aqueous solution containing an electrolyte salt and having a pH of 3 or more and less than 12, in which a thickener is further dissolved, and an aqueous solution in which a gelation promoter (polyvalent metal salt) is dissolved, into the exterior body of a battery, and mix the two in the exterior body, since the gel electrolyte can be formed more efficiently and well.
[0130] There are no particular limitations on the storage container for the air battery, and depending on the shape and structure of the waterproof device, a sheet-like storage container (sheet-like battery exterior body) as shown in Figures 2 and 3, a storage container made of a metal can formed of a metal exterior can, a metal sealing plate, and a resin gasket, etc., can be used. In the case of a storage container made of a metal can, it is preferable that it has a flat shape called a coin shape or a button shape.
[0131] The sheet-like storage container can be made of, for example, a resin film, and examples of such a resin film include nylon film (such as nylon 66 film), polyester film (such as PET film), etc. The thickness of the resin film is preferably 20 to 100 μm.
[0132] In addition, the sealing of the sheet-like container is generally performed by heat-sealing the end of the upper resin film and the end of the lower resin film of the sheet-like container, but in order to make this heat-sealing easier, a heat-sealing resin layer may be laminated on the resin film exemplified above and used for the sheet-like container. Examples of the heat-sealing resin constituting the heat-sealing resin layer include modified polyolefin films (such as modified polyolefin ionomer films), PP and copolymers thereof. The thickness of the heat-sealing resin layer is preferably 20 to 100 μm.
[0133] A metal layer may be laminated on the resin film. The metal layer may be made of an aluminum film (aluminum foil, including aluminum alloy foil), a stainless steel film (stainless steel foil), etc. The thickness of the metal layer is preferably 10 to 150 μm.
[0134] The resin film constituting the sheet-like storage container may be a film having a structure in which the above-mentioned heat-sealable resin layer and the above-mentioned metal layer are laminated together.
[0135] The shape of the storage container may be polygonal (triangle, quadrangle, pentagon, hexagon, heptagon, octagon) in plan view, or may be circular or elliptical in plan view. In the case of a sheet-like storage container that is polygonal in plan view, the positive electrode external terminal and the negative electrode external terminal may be drawn out from the same side or from different sides.
[0136] In the part of the container where the positive electrode is disposed, an air hole is formed to take in air into the battery. There is no particular limit to the number of air holes, and it is sufficient to select a number that can take in enough air to allow the air battery to discharge satisfactorily. There is also no particular limit to the shape of the air hole, and it may be circular in plan view, or may be elliptical or polygonal (triangle, square, etc.).
[0137] In an air battery, as shown in Fig. 3, a water-repellent film is usually disposed between the positive electrode and the container, and a film that is water-repellent but allows air to pass through is used as the water-repellent film. Specific examples of such water-repellent films include films made of resins such as fluororesins such as PTFE; and polyolefins such as PE and PP. The thickness of the water-repellent film is preferably 50 to 250 µm.
[0138] An air diffusion membrane for supplying air taken into the container to the positive electrode may be disposed between the container and the water-repellent membrane. The air diffusion membrane may be a nonwoven fabric made of a resin such as cellulose, polyvinyl alcohol, polypropylene, or nylon. The thickness of the air diffusion membrane is preferably 100 to 250 μm.
[0139] There is no particular limit to the thickness of the air battery (the length of a in FIG. 3 in the case of a sheet-type air battery), and it can be changed as appropriate according to the shape and structure of the waterproof device to which the air battery is applied. One advantage of a sheet-type air battery is that it can be made thin, and from this viewpoint, it is preferable that the thickness is, for example, 1 mm or less. Furthermore, in the case of a sheet-type air battery, the thickness is usually preferably 0.2 mm or more in order to ensure a certain capacity.
[0140] On the other hand, in the case of a flat storage container made of a metal can, the thickness is preferably about 3 to 5 mm.
[0141] The circuit section of the waterproof device may be configured according to the application of the waterproof device. For example, in the case of a medical patch in which the waterproof device detects biological information such as the body temperature of a wearer (subject) and injects a predetermined amount of a medicinal liquid into the wearer at a predetermined time, the circuit section may be configured to include a drive circuit section and a functional element for detecting predetermined data from the wearer (biological information such as body temperature, pulse rate, respiratory rate, etc.) and for administering a predetermined treatment (such as injection of a medicinal liquid) to the wearer.
[0142] When the waterproof device detects biological information such as the body temperature of the wearer, the functional element is preferably a thin member such as a sensor plate for detecting the biological information of the wearer, which is made of a thin plate or a thin film. Such a functional element can be realized in the form of, for example, a metal foil; a resin film having a conductive material such as metal or carbon disposed on the surface; or the like.
[0143] On the other hand, if the waterproof device is configured to inject a predetermined amount of medicinal liquid into the wearer at a predetermined time, the functional element can be configured to include a small injection needle, a medicinal liquid container containing the medicinal liquid to be injected into the wearer, and a pump unit that pushes the predetermined amount of medicinal liquid from the medicinal liquid container.
[0144] These functional elements are usually exposed from the exterior body, base material, and adhesive layer (bonding layer) so that they can be directly touched by the wearer's skin, as shown in Fig. 1, but depending on the function of the functional element, it may be possible to function without exposing it to the outside. For example, if the functional element has a function that can detect the wearer's biological information without directly touching the skin, the entire functional element can be housed, for example, within the space formed by the exterior body and base material, and no part is exposed to the outside.
[0145] The drive circuit section may have known thin-film electronic circuit components, such as wiring formed of a metal foil film such as copper on a film substrate; one or more electronic circuits formed as thin-film chips that function as memories, processors, transceiver circuits, etc.; and an antenna element formed of a metal foil film used for communication with the outside.
[0146] The drive circuit unit may be designed to have functions that are compatible with the application of the waterproof device. For example, in the case of a waterproof device that measures the wearer's body temperature, the temperature of the sensor plate, which is the functional element, may be detected, for example, by changes in the value of the current flowing through the sensor plate, and the measured body temperature value may be transmitted from the antenna element to the external device in response to a control signal from an external device such as a linked smartphone, or according to control by a logic circuit contained in the drive circuit unit itself.
[0147] Furthermore, when the functional element is a unit that injects medicinal liquid into the wearer, the drive circuit section may be provided with a function that enables a predetermined amount of medicinal liquid to be injected into the wearer at a predetermined time using a timer function provided in the drive circuit section or in accordance with an operation signal from an external device.
[0148] The drive circuit unit and the functional element can be connected, for example, by directly contacting a part of the functional element with at least a protruding portion of an electronic circuit component that constitutes the drive circuit unit, or by interposing a conductive means such as wiring between the drive circuit unit and the functional element.
[0149] The drive circuit unit and the battery, which is the power source, can be arranged so that the battery is stacked on the drive circuit unit, for example, as shown in FIG. 1. This allows the battery area to approach 100% relative to the area of the waterproof device. Therefore, compared to when the drive circuit unit and the battery are arranged side by side, the battery area can be made larger for the same area of the waterproof device, and a higher battery capacity can be achieved. On the other hand, when the battery area is the same, when the battery is arranged stacked on the drive circuit unit, the area of the waterproof device can be made smaller than when they are arranged side by side.
[0150] In addition, when the drive circuit unit and the battery are arranged in a stacked manner, the area of the drive circuit unit can be expanded to cover the entire area of the waterproof device, which increases the design margin for the arrangement of various circuit components in the drive circuit unit, and for example, the resistance value component can be reduced by shortening or thickening the connection wiring, thereby realizing a circuit unit that operates with lower power consumption. Furthermore, by arranging the drive circuit unit and the battery in a stacked manner, if the drive circuit unit has an antenna element, the area of the antenna element can be increased to improve the antenna characteristics, and thinner circuit components can be selected even if they are relatively large in area, thereby making the drive circuit unit and the entire waterproof device thinner.
[0151] However, if the storage container contains a metal material, such as a laminate film with a metal layer, it is preferable to adjust the battery placement so that the battery storage container does not cover the antenna element, in order to avoid impeding the communication function of the waterproof device.
[0152] On the other hand, in cases where the waterproof device becomes too thick, making it difficult to attach to the skin or causing the wearer to feel a strong sense of discomfort, the circuit unit and air battery can be arranged side-by-side rather than stacked, thereby preventing an increase in the overall thickness of the waterproof device.
[0153] The waterproof device may be formed with an adhesive layer for attachment to the body as necessary, as shown in Fig. 1. There are no particular limitations on the configuration (material, thickness, etc.) of the adhesive layer, and for example, the same material (acrylic adhesive, rubber adhesive, silicone adhesive, hydrogel, etc.) used for the adhesive layer for attachment to the body in known body-worn devices (medical patches, etc.) and bandages may be used, and the thickness may be such that the waterproof device can be attached and maintained well on the body, for example, 30 to 1000 µm.
[0154] It should be noted that the waterproof device does not need to have an adhesive layer if it can be attached to the body by means other than the adhesive layer (such as a rubber band).
[0155] The waterproof device disclosed in the present application can be used for the same purposes as conventionally known body-worn devices, such as medical patches as wearable patches.
[0156] Second Embodiment Next, a second embodiment of the waterproof device disclosed in the present application will be described.
[0157] The waterproof device of the second embodiment is a wearable patch that is worn directly on the body, and differs from the waterproof device of the first embodiment described above in that it uses a sheet-shaped air battery as a power source, and the sheet-shaped battery exterior body (sheet-shaped storage container) on the outer surface side of the sheet-shaped air battery constitutes part of the exterior body that is the outer shell member of the entire waterproof device.
[0158] FIG. 4 is a cross-sectional view illustrating the overall configuration of a wearable patch according to the second embodiment.
[0159] FIG. 5 is a view of the wearable patch according to the second embodiment as viewed from the outer surface side.
[0160] Fig. 4 shows a cross section of the portion indicated by A-A' in Fig. 5. In Fig. 4, the upper surface of the wearable patch 200 in the figure is the outer surface, and the lower surface in the figure is the inner surface. In order to avoid complicating the figure, Fig. 5 shows only the positions of the main components in the wearable patch according to this embodiment.
[0161] In the following description of this embodiment, the upper side in FIG. 4 will be referred to as the outer surface side, and the lower side in FIG. 4 will be referred to as the inner surface side, where appropriate.
[0162] Furthermore, the following description of the embodiments is merely an example, and the components constituting the wearable patch according to the present disclosure are not limited to those described below.
[0163] The wearable patch 200 described in this embodiment is, for example, a medical patch that detects the body temperature of a wearer, and is used by being attached directly to the skin.
[0164] As shown in Fig. 4, the wearable patch 200 according to this embodiment includes an outer shell member 210 on the outer surface side composed of a water-repellent, gas-permeable sheet constituting the outer shell, an inner shell member 220 on the inner surface side corresponding to the base material, an air battery as a sheet-shaped battery in which the outer shell member 210 is one of the sheet-shaped battery exterior bodies and the power generating element 230 is enclosed between the outer shell member 210 and the other sheet-shaped battery exterior body 235, a drive circuit section 240 arranged on the inner surface side of the sheet-shaped battery exterior body 235 of the air battery, a functional element 250 that contacts the skin of the wearer, and an adhesive layer (adhesive layer) 260 formed on the inner surface side of the outer shell member 220 on the inner surface side of the wearable patch 200 in an area other than the part where the functional element 250 is arranged. In the wearable patch 200 of this embodiment, the outer shell member 220 on the inner surface side is formed in an area excluding the part where the functional element 250 arranged in contact with the drive circuit section 240 is formed.
[0165] The air battery is configured as a flexible sheet as a whole by forming each member constituting the power generating element 230, including the positive electrode 231 and the negative electrode 232, into a sheet shape. In the wearable patch 200 according to this embodiment, the portion of the outer shell member 210 on the positive electrode 231 side of the air battery facing the positive electrode 231 is formed of a water-repellent porous sheet so that air, which is a positive electrode active material, can be supplied to the positive electrode 231 when the wearer wears the wearable patch 200.
[0166] In this way, the battery exterior body on the positive electrode 31 side of the sheet-type battery can be used as the outer shell member of the wearable patch 100, and since the number of components can be reduced compared to when, for example, the sheet-type air battery is disposed inside the outer shell member of the wearable patch, the entire device can be simplified in configuration, and the device can be made smaller, lighter, and less expensive. In addition, by forming the outer shell member 210 facing the positive electrode 231 of the air battery from a water-repellent porous sheet, air can be stably supplied to the positive electrode 231 of the sheet-type air battery when the wearer is wearing the wearable patch 200.
[0167] In addition, in the wearable patch 200 shown in this embodiment, the drive circuit unit 240 and the sheet-shaped air battery are stacked, so that the ratio of the area of the air battery to the area of the wearable patch 200 can be increased, thereby achieving a large battery capacity.
[0168] Furthermore, the wearable patch 200 according to the present embodiment includes a thin member formed of a thin plate or thin film, such as a sensor plate for detecting the body temperature of a wearer, as the functional element 250. When a thin functional element 250 is included, as shown in FIG. 4, the functional element 250 can be arranged by being layered with the drive circuit section 240.
[0169] In this way, by stacking the functional element 250 with the drive circuit section 240, the area of the drive circuit section 240 can be made larger relative to the overall area of the wearable patch 200, which increases the design margin for the placement of various circuit components in the drive circuit section 240, and for example, the resistance component can be reduced by shortening or thickening the connection wiring, thereby realizing a drive circuit section 240 that operates with lower power consumption. Furthermore, when an antenna element is provided, the area can be increased to improve the antenna characteristics, or a circuit component that is relatively large in area but thinner can be selected, thereby making the drive circuit section 240, and ultimately the entire wearable patch 200, thinner.
[0170] In addition, since the functional element 250 is configured to be arranged in a layered manner with the drive circuit section 240, the functional element 250, which is a sensor plate, can be arranged in approximately the center of the wearable patch 200 when viewed in a plan view, as shown in Fig. 5. In this manner, the adhesive layer 260 can be formed around the functional element 250, so that the wearable patch 200 can be firmly attached to the skin by the adhesive of the adhesive layer 260, and the functional element 250, which is a sensor plate, can be maintained in close contact with the skin of the wearer even when the wearer moves or sweats, or when water gets on the part where the wearable patch 200 is attached.
[0171] The air battery, drive circuit, functional element, and even the configuration of the film members such as the outer shell member and base material, the battery outer shell, and the material of the adhesive layer (adhesive layer) that constitute the wearable patch 200 of the second embodiment are similar to those described in the first embodiment above, and therefore will not be described repeatedly. EXAMPLES
[0172] The present invention will be described in detail below based on examples of the waterproof device disclosed in the present application, although the following examples are not intended to limit the waterproof sheet disclosed in the present application.
[0173] Example 1 [Preparation of sheet-shaped air battery] <Positive electrode> DBP oil absorption 495cm 3 / 100g, specific surface area 1270m 2 A catalyst-containing layer-forming composition was prepared by mixing 30 parts by mass of carbon (Ketjen Black EC600JD (Lion Specialty Chemicals)) of 1.0 g / g, 15 parts by mass of an acrylic dispersant, 60 parts by mass of SBR, and 500 parts by mass of water.
[0174] A porous carbon paper [thickness: 0.25 mm, porosity: 75%, air permeability (Gurley): 70 sec / 100 ml] was used as the porous conductive substrate, and the catalyst-containing layer-forming composition was applied in a coating amount of 10 mg / cm 2 after drying. 2 The substrate surface was coated with the solution in stripes so that the solution was as follows: and then dried to obtain a porous conductive substrate having a portion where the catalyst-containing layer was formed and a portion where the catalyst-containing layer was not formed. This porous conductive substrate was punched out into a shape having a main body portion measuring 15 mm x 15 mm where the catalyst-containing layer was formed and a terminal portion measuring 5 mm x 15 mm where the catalyst-containing layer was not formed, to produce a positive electrode (air electrode) with an overall thickness of 0.27 mm.
[0175] <Negative electrode> A zinc alloy foil (thickness: 0.05 mm) containing 0.05% In, 0.04% Bi, and 0.001% Al as additive elements was punched out into a shape having a main body measuring 15 mm x 15 mm and a terminal part measuring 5 mm x 15 mm to prepare a negative electrode with a theoretical capacity of approximately 65 mAh.
[0176] <Electrolyte> The electrolyte used was an aqueous solution of ammonium sulfate with a concentration of 20% by mass (pH was 5.3 as measured at 25° C. using a HORIBA, Ltd. “LAQUA twin compact pH meter”).
[0177] <separator> The separator used was made of two graft films (thickness per film: 15 μm) composed of a graft copolymer having a structure in which acrylic acid is graft-copolymerized onto a polyethylene main chain, placed on either side of a cellophane film (thickness: 20 μm) (total thickness: 50 μm).
[0178] <Water-repellent film> The water-repellent film was a porous PTFE sheet with a thickness of 200 μm.
[0179] <Sheet-type storage container> A sheet-like storage container was made using two sheets of aluminum laminate film (thickness: 65 μm) measuring 25 mm×25 mm, which had a PET film on the outer surface of the aluminum foil and a polypropylene film as a heat-sealing resin layer on the inner surface.
[0180] In one of the aluminum laminate films, nine air holes with a diameter of 0.5 mm were formed in advance at equal intervals of 4.5 mm length × 4.5 mm width (the center-to-center distance between the air holes was 5 mm) in a regular pattern, and the water-repellent film was heat-welded to the inner surface using a hot melt resin. In addition, in the other aluminum laminate film, a modified polyolefin ionomer film was attached parallel to the sides of the exterior body to the part where the positive and negative electrode terminals were to be located.
[0181] <Battery assembly> The aluminum laminate film having a water-repellent film was placed underneath, and the positive electrode, the separator, and the negative electrode were laminated in that order on the water-repellent film, and then another aluminum laminate film was placed on top of the terminals of the positive electrode and the negative electrode so that the modified polyolefin ionomer film was positioned on top of them. Next, the three sides of the two aluminum laminate films were heat-sealed together to form a bag, and 0.1 ml of the electrolyte was poured through the opening, and the opening was then heat-sealed to seal the bag, producing a sheet-shaped air battery with a thickness of about 1.2 mm (length a in FIG. 3).
[0182] [Preparation of waterproof device] A waterproof device was produced as follows using a measurement unit having a driving circuit section having a memory, a processor, a transceiver circuit, and an antenna element mounted on a flexible film substrate, and further comprising a circuit section having an element for measuring the wearer's body temperature as a functional element.
[0183] After the sheet-type air battery was conductively connected to the connection terminal of the circuit section, the sheet-type air battery was placed on the circuit section so that the surface having the air holes was opposite to the circuit section to form a stacked unit. Although not shown in the figure, the position of the sheet-type air battery was adjusted so that the upper part of the antenna element was not covered by the aluminum laminate film of the sheet-type air battery in order to prevent the communication function of the transmission and reception circuit from being hindered.
[0184] Next, two sheets of a laminated sheet of a PE porous sheet and a PET nonwoven sheet ("Breathlon BRN3000E1" (product name) manufactured by Nitoms Corporation, thickness: 0.25 mm, water pressure resistance: >80 kPa, air permeability: 400 sec / 100 ml) cut to a size of 50 mm x 50 mm were prepared as water-repellent and air-permeable sheets. An opening was provided in the center of one of the water-repellent and air-permeable sheets to match the size of the functional element of the laminated unit, to prepare a substrate.
[0185] Furthermore, the film substrate of the laminate unit was adhered to the PE porous sheet of the base material such that the functional element was exposed from the opening, thereby integrating the base material and the laminate unit.
[0186] Another water-repellent, air-permeable sheet, which would serve as the outer casing, was placed on top of the stacked unit with its PE porous sheet facing the sheet-shaped air battery, and a waterproof device was produced by thermally welding the PE porous sheets together around the peripheral edges of each water-repellent, air-permeable sheet.
[0187] The waterproof device can be attached to the body by forming an adhesive layer on the lower surface of the base material as shown in FIG. 1 or by attaching a rubber band or the like.
[0188] Example 2 A waterproof device was produced in the same manner as in Example 1, except that the water-repellent, breathable sheet was changed to a laminated sheet of a PE porous sheet and a nylon nonwoven sheet ("Breathlon BRN1860" (product name) manufactured by Nitto Corporation, thickness: 0.35 mm, water pressure resistance: >80 kPa, air permeability: 4500 sec / 100 ml).
[0189] Example 3 A waterproof device was produced in the same manner as in Example 1, except that the water-repellent, breathable sheet was changed to a laminated sheet of a PE porous sheet and a PET nonwoven sheet, which had a different breathability from that used in Example 1 ("BREATHRON BRN-A12OE1" (product name) manufactured by Nitoms Corporation, thickness: 0.25 mm, water pressure resistance: >80 kPa, breathability: 28000 sec / 100 ml).
[0190] Example 4 A waterproof device was produced in the same manner as in Example 1, except that the water-repellent, air-permeable sheet was changed to a PTFE porous sheet (Sumitomo Electric Industries, Ltd. "WP-020-80", thickness: 0.1 mm, water pressure resistance: 170 kPa, air permeability: 2500 sec / 100 ml) and a PP sealing material was sandwiched around the periphery of each water-repellent, air-permeable sheet before heat welding.
[0191] Example 5 A waterproof device was produced in the same manner as in Example 1, except that the water-repellent, breathable sheet was changed to a PE nonwoven fabric (thickness: 0.17 mm, water pressure resistance: 20 kPa, air permeability: 250 sec / 100 ml) and the peripheral edges of each PE nonwoven fabric were heat-welded to each other.
[0192] Comparative Example 1 A waterproof device was produced in the same manner as in Example 1, except that the water-repellent, breathable sheet was changed to a PE nonwoven fabric (thickness: 0.25 mm, water pressure resistance: 5 kPa, air permeability: 2 sec / 100 ml) and the peripheral edges of each PE nonwoven fabric were heat-welded to each other.
[0193] Comparative Example 2 A waterproof device was produced in the same manner as in Example 1, except that a non-permeable, non-porous PP film (thickness: 0.05 mm, water pressure resistance: >80 kPa, air permeability: >100,000 sec / 100 ml) was used instead of the water-repellent, air-permeable sheet, and the peripheral edges of each PP film were heat-welded to each other.
[0194] The waterproof devices of Examples 1 to 5 and Comparative Examples 1 and 2 were subjected to the following evaluations.
[0195] (Water immersion test) Each waterproof device was immersed in water 1 m deep for 30 minutes in accordance with the method specified in JIS C 0920, and after being removed from the water, the exterior body was cut open and the water resistance of each waterproof device was evaluated by visually checking whether water had entered the inside of the device.
[0196] (Checking the operation of air batteries) After assembling each waterproof device, the devices were left in a room at 35°C and 60% relative humidity, and the time until they could no longer receive information sent from the device was measured to confirm the operating time of the air battery under dry conditions.
[0197] Next, after assembly, each waterproof device (different from the one used to measure operating time under dry conditions) was immersed in water 1m deep for 30 minutes, and then removed from the water and left to stand in a room at 35°C and a relative humidity of 60%.The time until it was no longer possible to receive information sent from the device was measured, and the operating time of the air battery under wet conditions was confirmed.
[0198] The configurations of the water-repellent, breathable sheets used in the exterior bodies of the waterproof devices of the Examples and Comparative Examples are shown in Table 1. Furthermore, the results of the above evaluation, expressed as 100 for the operating time of the air battery under dry conditions of the waterproof device of Example 1, are shown in Table 2.
[0199] [Table 1]
[0200] [Table 2]
[0201] As shown in Tables 1 and 2, the waterproof devices of Examples 1 to 5, in which the circuit section and battery were protected by an exterior body made of a water-repellent, breathable sheet with appropriate water pressure resistance, were able to operate the sheet-type air battery even after being immersed in water, and their functionality was maintained well.
[0202] On the other hand, the waterproof device of Comparative Example 1, which had an exterior body made of a sheet with too low water pressure resistance, had insufficient water resistance and water penetrated into the inside of the device when immersed in water, blocking the air flow path and preventing air from being supplied to the positive electrode of the sheet-type air battery, making it impossible to operate the device. Also, the waterproof device of Comparative Example 2, which had an exterior body made of a non-porous PP film, had good water resistance, but the inflow of air into the inside was blocked by the exterior body, making it practically impossible to discharge the sheet-type air battery, and the device could not be operated regardless of the conditions.
[0203] (Characteristics Evaluation of the Wearable Patch According to the Second Embodiment) Next, a description will be given of the results of a study in which the discharge capacity of the wearable patch described in the second embodiment was measured and compared when the electrolyte of the air battery was changed.
[0204] In each sheet-type air battery, the following materials were used for the positive electrode, negative electrode, electrolyte, separator, water-repellent film, and exterior body.
[0205] <Positive electrode> DBP oil absorption 495cm 3 / 100g, specific surface area 1270m 2 A composition for forming a catalyst layer was prepared by mixing 30 parts by mass of carbon (Ketjen Black EC600JD (product name: manufactured by Lion Specialty Chemicals)) of 1.0 g / g, 15 parts by mass of an acrylic dispersant, 60 parts by mass of SBR, and 500 parts by mass of water.
[0206] A porous carbon sheet (thickness: 0.25 mm, porosity: 75%, air permeability (Gurley): 70 sec / 100 ml) was used as a current collector, and the catalyst layer forming composition was applied in an amount of 10 mg / cm2 after drying. 2 The substrate surface was coated with the solution in stripes so that the solution was dried, thereby obtaining a current collector having a portion where the catalyst layer was formed and a portion where the catalyst layer was not formed. This current collector was punched out into a shape with a catalyst layer size of 15 mm x 15 mm and a lead portion with a size of 5 mm x 15 mm at one end where the catalyst layer was not formed, to produce a positive electrode (air electrode) with an overall thickness of 0.27 mm.
[0207] <Negative electrode> A zinc alloy foil (thickness: 0.05 mm) containing 0.05% In, 0.04% Bi, and 0.001% Al as additive elements was punched out into a shape having a 15 mm x 15 mm portion that would function as the active material and a 5 mm x 15 mm portion at one end that would serve as a lead to prepare a negative electrode.
[0208] <Electrolyte> Battery 1: 20% ammonium sulfate solution (pH = 5.3) Battery 2: 20% ammonium chloride solution (pH = 4.3) Battery 3: 20% by weight sodium chloride aqueous solution (pH=7) Battery 4: 30% by mass potassium hydroxide aqueous solution (pH=14).
[0209] <separator> Two graft films (thickness per film: 15 μm) composed of a graft copolymer having a structure in which acrylic acid is graft-copolymerized onto a polyethylene main chain were used, which were placed on either side of a cellophane film (thickness: 20 μm).
[0210] <Water-repellent film> A PTFE sheet with a thickness of 200 μm was used.
[0211] <Battery exterior body> An aluminum laminate film measuring 2.5 cm x 5 cm was used to constitute the battery exterior body on the positive electrode side and to serve as the outer shell member, with the aluminum foil having a PET film on the outer surface and a polypropylene film on the inner surface as a heat-sealed resin layer, and an aluminum laminate film measuring 2.5 cm x 2.5 cm was used to constitute the exterior body on the negative electrode side.
[0212] <Battery assembly> In the laminate film for constructing the outer shell member, one laminate film placed on the positive electrode side had nine air holes with a diameter of 0.5 mm formed in a matrix at equal intervals of 4.5 mm length x 4.5 mm width (the center-to-center distance between air holes was 5 mm) corresponding to the position of the catalyst layer of the positive electrode, and a water-repellent film was heat-sealed to the inner surface using hot melt resin. In addition, in the laminate film for constructing the negative electrode exterior body, a modified polyolefin ionomer film was attached parallel to the side of the exterior body to the part where the positive and negative electrode leads are placed, in order to improve the sealing of the heat-sealed part between the leads and the exterior body.
[0213] The laminate film for constituting the outer shell member was placed on the bottom, and the positive electrode, the separator, and the negative electrode were laminated in order on the water-repellent film, and the laminate film for constituting the negative electrode side exterior body was placed on top of the leads of the positive electrode and the negative electrode so that the modified polyolefin ionomer film was positioned on top of the leads of the positive electrode and the negative electrode. Next, the laminate films for constituting the negative electrode side exterior body were heat-sealed to each other on three sides around the laminate film to form a bag, and the electrolyte was poured from the opening, and the opening was then heat-sealed to seal the bag to form a sheet-shaped air battery. The thickness of the battery produced was approximately 1 mm.
[0214] The air battery thus fabricated was left in the atmosphere for 10 minutes, and then discharged to 0.5 V at a current equivalent to a 100-hour rate relative to the design capacity of the battery, and the discharge capacity was measured. The results are shown in Table 3.
[0215] [Table 3]
[0216] In comparison with the air battery (battery 4) using a high-concentration alkaline electrolyte used as the electrolyte in commercially available button-type air batteries, the air batteries (batteries 1 to 3) using safer electrolytes were also able to obtain sufficient discharge capacity. In particular, batteries 1 and 2, which used a salt of a strong acid and a weak base as the electrolyte salt, obtained excellent characteristics on a par with battery 4, which had the same composition as the electrolyte in commercially available button-type air batteries.
[0217] From the above results, it can be seen that the air battery described in the above embodiment is thin, easy to handle, highly safe, and has a relatively large capacity, making it suitable as a power source for devices worn directly on the body.
[0218] By stacking the battery with a driving circuit unit described below and an outer shell member on the inner surface side measuring 2.5 cm x 5 cm, a wearable patch can be constructed in which the exterior body of the battery serves as the outer shell member on the outer surface side of the entire patch.
[0219] As described above, in the waterproof device disclosed in the present application, at least a part of the exterior body is made of a water-repellent, breathable sheet having a water pressure resistance of 12 kPa or more, so that an air battery that requires air (oxygen) as the positive electrode active material can be used as the operating power source housed inside the exterior body. In addition, in the wearable patch as a waterproof device disclosed in the present application, the outer shell member on the outer surface side constituting the main body of the patch is configured to also serve as the battery exterior body on the outer surface side of the air battery as a driving power source, which is housed between the outer shell member and the outer shell member on the inner surface side formed opposite to it. Therefore, the number of components can be reduced compared to when the outer shell of the wearable patch is placed inside the component and the air battery is placed. Furthermore, in an air battery that uses air as the positive electrode active material, it is necessary to communicate the surface of the positive electrode with the outer space of the wearable patch, but in the wearable patch of this embodiment, the outer shell member also serves as the battery exterior body on the positive electrode side of the air battery, so that the outer shell member facing the positive electrode only needs to be made of a water-repellent breathable sheet, and compared to a configuration in which it is necessary to form an opening for passing air in both the exterior body on the positive electrode side and the outer shell member of the wearable patch, the manufacturing process of the wearable patch can be further simplified and costs can be reduced.
[0220] In addition, a resin film laminated with a metal thin film such as aluminum foil can be used as the battery exterior of the air battery. In this way, leakage of the electrolyte enclosed inside the battery exterior can be more reliably prevented, but if the entire outer shell member on the outer surface side is formed as a laminate of a resin film and a metal thin film, the antenna element formed in the drive circuit unit may be shielded, which may interfere with communication between the drive circuit unit and external devices.
[0221] For this reason, it is preferable to adjust the shape and arrangement of the outer shell member and leads so that metal components such as the metal thin film of the outer shell member on the outer surface side are not placed on top of the antenna element of the drive circuit unit, thereby preventing interference with communication with the outside.
[0222] For example, radio waves can be prevented from being shielded by arranging the antenna element of the drive circuit unit away from other circuit parts, by providing a notch in the outer shell member to expose the antenna element, etc. Furthermore, if the communication means between the drive circuit unit and an external device is infrared communication, a part of the outer shell member on the outer surface side can be made transparent to allow infrared rays to pass through.
[0223] In the above embodiment, a liquid electrolyte is used in the air battery, but by using a gelled electrolyte material, the material constituting the exterior body of the air battery can be formed from a resin film without a metal foil laminated thereon. Furthermore, in this case, the air battery can be formed by printing, which further simplifies the manufacturing process of the wearable patch.
[0224] In addition, in the above embodiment, an example was shown in which a water-repellent porous sheet was used as the outer shell member on the outer surface side in the portion facing the positive electrode formation region, but it is preferable to construct at least the portion of the outer shell member facing the positive electrode formation region from a resin nonwoven fabric.
[0225] Furthermore, the sheet battery that is the driving power source is not limited to the air battery described above, and known sheet batteries such as manganese batteries can be used as long as their capacity is suitable for the intended use of the wearable patch. Even in this case, it is not necessary to form the outer shell member on the outer surface side or the exterior body of the sheet battery with a metal foil laminate. Also, there is no need to place the positive electrode on the outer surface side, as in the case of an air battery.
[0226] Furthermore, in the above embodiment, a configuration in which an outer shell member is provided on the inner surface side of the wearable patch has been described, but since the drive circuit unit can be formed as a resin sheet, this inner surface side outer shell member is not an essential component of the wearable patch according to this embodiment. When an outer shell member is not provided on the inner surface side of the wearable patch, the adhesive layer is formed directly on the inner surface side of the drive circuit unit formed as a resin sheet and the inner surface side of the outer shell member on the outer surface side.
[0227] Furthermore, in the above embodiment, a configuration has been described in which the drive circuit is laminated in the arrangement region of the power generating element of the air battery, and further, the functional element is laminated on the drive circuit, that is, the arrangement positions of the power generating element of the air battery, the drive circuit, and the functional element all overlap when the wearable patch is viewed in plan as shown in Fig. 5. However, in the waterproof device and wearable patch disclosed in the present application, it is not essential that the air battery, the drive circuit, and the functional element are all laminated.
[0228] For example, as described above, a means for communicating with an external device, such as an antenna terminal of the drive circuit unit, can be positioned offset from the power generating element of the air battery in the direction of the main surface of the wearable patch.
[0229] In the above embodiment, a thin-film sensor plate for detecting the body temperature, heart rate, etc. of the wearer is used as the functional element, but the wearable patch disclosed in the present application can be configured as a medical device with a drug administration function for injecting a drug solution into the wearer. In the case of a functional element with a drug administration function, a tank for storing the drug solution and a mechanism for supplying a predetermined amount of the drug solution at a predetermined timing are required, and the thickness of the functional element becomes thick. In such a case, the functional element can be arranged to be shifted from the position of at least one of the air battery and the driving circuit in the main surface direction of the wearable patch, thereby preventing the thickness of the wearable patch from increasing, and the wearer can wear the wearable patch without feeling uncomfortable, even if the area of the wearable patch becomes large.
[0230] [Note] In the second embodiment of the present application, a configuration in which the exterior body on the positive electrode side of an air battery also serves as the exterior body for the entire device has been described as an example in which the configuration is applied to a waterproof device in which the exterior body for the entire device is made of a water-repellent, breathable sheet.
[0231] However, the configuration in which the battery exterior of the sheet-type air battery also serves as an exterior as an outer shell member of the device, as exemplified using a wearable patch as the second embodiment, can be applied to various devices other than wearable patches equipped with an air battery, a driving circuit, and functional elements, in which the entire exterior is made of a sheet material other than a water-repellent, breathable sheet.
[0232] In this case, the exterior body constituting the outer shell member of the entire device can be made of a resin sheet (a sheet made of a resin such as PE, PP, polyethylene terephthalate, nylon, etc.), etc. Also, an air hole for supplying air is formed in at least the exterior body of the portion facing the positive electrode of the air battery (a member that serves both as the exterior body that is the outer shell member of the device such as a wearable patch and as the battery exterior body of the air battery), and the positive electrode is configured to communicate with the external space of the wearable patch.
[0233] In addition, for example, if there is no need for the wearable patch shown as the second embodiment to be waterproof, the configuration other than the outer casing on the front side can be the same as that shown in the second embodiment.
[0234] The appended claims for the configuration of the wearable patch when used in devices other than waterproof devices are described below. The device (wearable patch) configured as described below includes a functional element that contacts the skin, a drive circuit unit that operates the functional element, a sheet-shaped battery in which a power generating element including a positive electrode and a negative electrode is enclosed inside two sheet-shaped battery exterior bodies, and an adhesive layer formed on the inner surface, and the sheet-shaped battery exterior body on the outer surface side of the sheet-shaped battery constitutes a part of the exterior body that is the outer shell member on the outer surface side of the entire device. In this way, it is possible to achieve a simple configuration with a reduced number of components that constitute the device, compared to a configuration in which a battery that is an operating power source and a drive circuit unit are arranged inside the exterior member that is the exterior body that constitutes the outer shell of the device.
[0235] As a result, a device can be realized that uses a sheet-type battery with the capacity required to fulfill its function, while maintaining a small, lightweight form and causing little discomfort to non-wearers.
[0236] [Appendix 1] A wearable patch that is worn directly on the body, A functional element in contact with the skin; A drive circuit unit that operates the functional element; A sheet-like battery in which a power generating element including a positive electrode and a negative electrode is enclosed inside two sheet-like exterior bodies; An adhesive layer formed on the inner surface thereof, A wearable patch, characterized in that the sheet-like exterior body on the outer surface side of the sheet-like battery constitutes a part of the outer shell member on the entire outer surface side.
[0237] [Appendix 2] 2. The wearable patch of claim 1, wherein the drive circuit unit and the sheet-type battery are laminated.
[0238] [Appendix 3] 3. The wearable patch of claim 1, wherein the battery is an air battery, and an air hole is formed in a portion of the sheet-like exterior body arranged on the outer surface side facing the positive electrode. [Industrial Applicability]
[0239] As described above, the waterproof device disclosed in the present application is a device that has a circuit unit, a power source, and an exterior body that protects the circuit unit and the power source, and is worn on the body, and at least a part of the exterior body is made of a water-repellent, air-permeable sheet, and the water-repellent, air-permeable sheet has a water pressure resistance of 12 kPa or more. By having such a configuration, the waterproof device disclosed in the present application can withstand usage conditions that may result in immersion in water, and can use an air battery with a large battery capacity as an operating power source, thereby achieving long-term operation.
[0240] For this reason, the device is useful as a waterproof device for various applications, primarily in the medical field, such as for measuring the wearer's physical data and injecting medicinal fluids. [Explanation of symbols]
[0241] 1 Power supply (battery) 10 Sheet-type air battery 20 Positive electrode (air electrode) 20a Positive terminal 30 negative electrode 30a Negative electrode terminal 40 Separator 50 Water-repellent film 60 Sheet-shaped storage container (sheet-shaped battery exterior body) 61 Air Vent 100 Waterproof Devices 110 Drive circuit section (circuit section) 120 Exterior body 121 Water-repellent, breathable sheet 122 Base material 130 Adhesive layer 140 Functional elements (circuit section) 200 Wearable Patches 210 Outer shell member (outer surface side: positive electrode side outer casing) 220 Inner surface side shell member 230 Power generation elements 231 Positive electrode 232 Negative electrode 235 Negative electrode exterior body 240 Drive circuit section 250 Sensor plate (functional element) 260 Adhesive layer
Claims
1. A device that is worn on the body and has a circuit unit, a power source, and an exterior body that protects the circuit unit and the power source, The power source is a sheet-type air battery, The sheet-shaped air battery has an electrolyte solution containing 5 to 50 mass % of an ammonium salt of a strong acid selected from hydrochloric acid, sulfuric acid, and nitric acid and having a pH of 3 to 10, and has a metal material as an active material of a negative electrode; The negative electrode is made of a zinc alloy foil in which a portion functioning as an active material and a portion serving as a lead formed at one end thereof are integrated together, At least a portion of the exterior body is made of a water-repellent, gas-permeable sheet, A waterproof device, wherein the water-repellent, air-permeable sheet has a water pressure resistance of 12 kPa or more.
2. 2. The waterproof device according to claim 1, wherein the water-repellent, air-permeable sheet has an air permeability of 60,000 sec / 100 ml or less.
3. 3. The waterproof device according to claim 1, wherein the water-repellent, air-permeable sheet has a thickness of 0.01 to 3 mm.
4. The water-repellent, gas-permeable sheet is a laminated sheet of a water-repellent porous sheet and a support sheet, 4. The waterproof device according to claim 1, wherein the support sheet is a nonwoven fabric sheet or a rubber sheet.
5. 5. The waterproof device according to claim 4, wherein the porous sheet is made of polyethylene, polypropylene or polytetrafluoroethylene.
6. 5. The waterproof device according to claim 4, wherein the nonwoven fabric sheet is made of polyethylene, polypropylene, polyethylene terephthalate or nylon.
7. 5. The waterproof device according to claim 4, wherein the rubber sheet is a urethane rubber sheet or a silicone rubber sheet.
8. 8. The waterproof device according to claim 1, wherein the sheet-shaped air battery has an electrolyte solution having a pH of less than 7.
9. the circuit section has a functional element that contacts the skin and a drive circuit section that operates the functional element, The sheet-type air battery is configured by encapsulating a power generating element including a positive electrode and a negative electrode inside two sheet-type battery exterior bodies, The sheet-shaped battery exterior body on the outer surface side of the two sheet-shaped battery exterior bodies of the sheet-shaped air battery constitutes a part of the exterior body which is an outer shell member on the outer surface side of the entire waterproof disc, The waterproof device according to any one of claims 1 to 8, wherein the water-repellent, gas-permeable sheet is disposed in a portion of the sheet-type battery exterior body on the outer surface side facing the positive electrode of the sheet-type air battery.
10. The waterproof device according to claim 9 , wherein the drive circuit unit and the sheet-shaped air battery are stacked.
Citation Information
Patent Citations
Oxygen permselective film and cell using the film
JP1996173775A
Non-aqueous electrolyte battery
JP2008287925A
Battery using acid electrolyte
JP2010062073A
Filter material, filter, and device
JP2012011326A
Electrically rechargeable metal-air battery system and method
JP2013537686A